New Perspectives on Applied Industrial Tools and Techniques (Management and Industrial Engineering,, 2018)
This book disseminates the current trends among innovative and high-quality research regarding the implementation of conceptual frameworks, strategies, techniques, methodologies, informatics platforms and models for developing advanced industrial tools and techniques and their application in different fields. It presents a collection of theoretical, real-world and original research works in the field of applied industrial tools and techniques. The text goes beyond the state-of-the-art in the field of industrial and software engineering, listing successful applications and use cases of studies of new approaches, applications, methods, techniques for developing advanced industrial tools, methodologies and techniques and their application in different fields. The topics covered in this book are of interest to academics, researchers, students, stakeholders and consultants.